Guidelines for clinical evaluation of anti‐cancer drugs. Issue 7 (8th June 2021) - Minami, Hironobu; Kiyota, Naomi; Kimbara, Shiro; Ando, Yuichi; Shimokata, Tomoya; Ohtsu, Atsushi; Fuse, Nozomu; Kuboki, Yasutoshi; Shimizu, Toshio; Yamamoto, Noboru; Nishio, Kazuto; Kawakami, Yutaka; et al.
Abstract: Clinical studies intended for regulatory approval must demonstrate the clinical benefits of the drug in a target population. Clinical development of a drug proceeds by stepwise clinical studies; after safety and pharmacokinetics are evaluated and the recommended dosage and administration are determined, efficacy and safety are evaluated in an exploratory manner, and finally clinical benefits are compared with conventional standard therapies. Guidelines for the clinical evaluation of anti‐cancer drugs in Japan were established in 1991 and amended in 2006 after molecular‐targeted drugs were introduced. Recent progress in the development of drugs acting on the immune system and cancer genomic medicine targeting rare but important molecular subtypes have altered the strategy for development of anti‐cancer drugs. It is often difficult to conduct a confirmatory randomized controlled study using overall survival as the primary endpoint in rare molecular subtypes, and the primary evaluation of the efficacy of some drugs and subsequent approval is based on the tumor response. As conducting clinical studies for rare subtypes solely within Japan is difficult, drug development needs to be conducted within a global study. However, this requires robust monitoring to detect possible ethnic differences in pharmacokinetics and drug efficacy. Development using the conditional approval system for drugs enforced in 2020 may be considered, when clinical utility is evaluated based on surrogate endpoints. Because of these changes, we have revised the guidelines for the clinical evaluation of anti‐cancer drugs in Japan. To promote global development of anti‐cancer drugs involving Japan, the guidelines have been translated into English. Abstract : Recent progress in development of drugs acting on the immune system and cancer genomic medicine targeting rare but important molecular subtypes have altered the strategy for development of anti‐cancer drugs. As conducting clinical studies for rare subtypes solely within Japan is difficult, drug development needs to be conducted within a global study with monitoring possible ethnic differences. Because of these changes, we have revised the guidelines for the clinical evaluation of anti‐cancer drugs in Japan.